Integrated microfluidic system for cell co-culture and simulation of drug metabolism. Issue 59 (7th June 2016) - Jie, Mingsha; Li, Hai-Fang; Lin, Luyao; Zhang, Jie; Lin, Jin-Ming
Abstract : We present a microfluidic integrator for cell cocultivation and simulation of pharmaceutical kinetic processes of oral drugs including intestinal absorption, liver metabolism, and anticancer activity. Abstract : In this work, a multi-type cell microfluidic integrator for cocultivation and enabling simulation of drug absorption, metabolism, and anticancer activity was developed. To organize an in vitro drug absorption and metabolism model, Caco-2, HepG2, and U251 cells were co-cultured as mimics of the intestine, liver, and glioblastoma, respectively. The HepG2 cell channel was separated from the Caco-2 cell channel by a polycarbonate semipermeable membrane, and connected with the U251 cell channel by a narrow channel array. Microfluidic cell co-culture, irinotecan (CPT-11) metabolism and cytotoxic analysis were performed simultaneously on the chip. This mimic organ-to-organ network carried out long-distance drug transfer under a microflow environment. The drug cytotoxicity assay was monitored by fluorescence visualization. The extra-/intra-cellular CPT-11 and its active metabolite of 7-ethyl-10-hydroxycamptothecin (SN-38) were qualitatively and quantitatively characterized by liquid chromatography-tandem mass spectrometry. It was revealed that prodrug CPT-11 was absorbed by Caco-2 cells and transferred to HepG2 cells through the porous membrane, then CPT-11 transformed to active SN-38 by HepG2 cells. Metabolic SN-38 was pumped out of HepG2 cells and diffused from the HepG2 cell channel toward the U251 cell channel through a connection channel array to targeting U251 cells. Our results suggest that this dynamic 3D device provides a potential application for high throughput drug screening and personalized cancer therapy.